2017
DOI: 10.5114/amsad.2017.72532
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anxiety and depression in hospitalized patients with first episode of acute myocardial infarction

Abstract: IntroductionEvaluation of anxiety and depression in cardiac patients is an area of nursing practice that is frequently neglected. The aim of the study was to explore anxiety and depression in hospitalized patients with their first episode of acute myocardial infarction.Material and methodsThe study sample included 148 hospitalized patients who had a first episode of acute myocardial infarction. Data collection was performed by the interview method using a specially designed questionnaire which included socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
(31 reference statements)
0
11
0
2
Order By: Relevance
“…In perspective of mental health screening among cardiac patients, focus should be given to females and less educated patients. The higher rates of depression and anxiety seen in these sub-groups were previously described in literature [34, 37, 40, 41]. Women seem to be more vulnerable to the trauma caused by cardiac events, which leads to a deterioration in depression and anxiety symptoms [37].…”
Section: Discussionmentioning
confidence: 69%
“…In perspective of mental health screening among cardiac patients, focus should be given to females and less educated patients. The higher rates of depression and anxiety seen in these sub-groups were previously described in literature [34, 37, 40, 41]. Women seem to be more vulnerable to the trauma caused by cardiac events, which leads to a deterioration in depression and anxiety symptoms [37].…”
Section: Discussionmentioning
confidence: 69%
“…Relatives of patients admitted to critical care units experience a significant level of anxiety due to various causes such as the stressful environment, risk of death for patients, and negligence of relatives' needs. (6) Most ICU admissions are unplanned and urgent, which contribute to severe anxiety of the family members. (24) Spiritual health of relatives of CCU patients was high in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…(5) The stressful critical care unit environment, critically ill patients who need immediate specialized monitoring, high mortality risk, complex technical and medical equipment, permanent monitoring of patients, alarm sounds, and restricted visiting hours are the factors affecting anxiety in relatives of critical care patients. (6) Some studies have shown that anxiety level in family members and first-degree relatives of CCU patients is equal to the anxiety level of the patients themselves. (7) The prevalence of anxiety varied from 15% to 24% in caregivers after discharge of their patients from the intensive care unit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute Coronary Syndrome (ACS) is one of the most common health problems in the world and the main cause of death. Significantly, causing more than 17.3 million deaths per year worldwide (Alexandri et al, 2017). In addition, SKA is the most important determinant of the most difficult chronic heart failure and most often causes permanent disability (Hodzic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%